The Role of Bhabinkamtibmas in Preventing the Serious Theft During Covid-19 Pandemic in Legal Region of Polrestabes Surabaya - Achmad Safiudin (Indonesian Journal of Police Studies, 2021)
During the Covid-19 pandemi, which began in 2019, it disrupted all aspects of society especially in security and orderliness. One of the examples is the number of criminal acts of the theft case in Polrestabes Surabaya jurisdiction is increasing. Bhabinkamtibmas is the figure of future police which is prioritizes prevention in the implementation of its duties through the pre-emptive and preventive functions. Bhabinkamtibmas provides counseling, guidance, accommodating complaints, hopes and social problems of residents, as well as finding solutions to these problems. Bhabinkamtibmas is also very influential in order to carrying out its duties. In terms to preventing criminal acts, one of it is the serious theft action. This thesis aims to describes the condition of Bhabinkamtibmas in Polrestabes Surabaya, in preventing the serious theft action and the factors that also affect the performance of it. This thesis is prepared by using a qualitative approach and field research type. The qualitative approach is implemented because it needs a direct approach to get the actual data about Bhabinkamtibmas. Field research type is flexible and evolve as suitable as the reality that discovered by the researcher. The results of this study is indicating that the role of Bhabinkamtibmas in preventing serious theft at Polrestabes Surabaya has not run optimally. There are many factors that influence it, one of the examples is Bhabinkamtibmas duties are very hampered caused by Covid-19 pandemi. Bhabinkamtibmas does effort to optimize the role of it, by using social media as supporting facilitiy for its job and make an innovation so the serious theft prevention can be easily achieved.